Extraction of value-added compounds from biomass using alternative solvents - Faria, Emanuelle Lima Pache de (2020)
The main objective of the present work was to investigate the potential of aqueous solutions of ionic liquids (ILs) and deep eutectic solvents (DES) as alternative solvents to extract value-added compounds from biomass and related waste. These compounds include triterpenic acids (TTAs; ursolic, oleanolic and betulinic acids), a sesquiterpene lactone (cynaropicrin) and a phenolic compound (syringic acid), whereas the biomass samples investigated correspond to olive tree leaves, apple and pear peels, and cardo leaves. The interest on the described natural compounds is related to their wide variety of biological properties, with relevant applications in the food, cosmetic and pharmaceutical industries. The developed work was focused on developing more sustainable and cost-effective extraction/recovery strategies than those commonly used. To this end, a better understanding on the solubilisation mechanisms (by hydrotropic or micelle-based effects) was also searched. It was demonstrated the enhanced capacity of aqueous solutions comprising surface-active ILs to extract TTAs, achieving yields up to 2.5 wt.% from olive tree leaves and up to 2.6 wt.% from apple peels, which are higher to those obtained with conventional organic solvents under similar conditions. An increase of 8 orders of magnitude in the solubility of ursolic acid in aqueous solutions of IL was verified when compared to pure water. Aqueous solutions of surface-active ILs were also demonstrated to be promising solvents to extract cynaropicrin from cardo leaves, leading to extraction yields up to 3.7 wt.% under the best identified conditions. Water was added as an anti-solvent, leading to the precipitation and recovery of 65 wt.% of cynaropicrin. Aqueous solutions of hydrotrope-based ILs were applied to extract of syringic acid from Rocha pear peels, leading to extraction yields up to 2.1 wt.% by reusing the solvent and up to 2.2 wt.% by reusing the biomass. These improvements in the extraction yield allowed to propose an extraction continuous process operating in countercurrent, in which the solvent and biomass are reused in a continuous mode. Taking advantage of the syringic acid solubility dependence with the IL concentration in aqueous solutions, where an enhancement up to 84-fold was obtained, water was again added as an anti-solvent allowing to recover 77 wt.% of syringic acid. In addition to the ILs aqueous solutions investigated, DES aqueous solutions were finally investigated for the extraction of cynaropicrin from cardo leaves, with extraction yields up to 6.2 wt%. These results are higher than those obtained with pure DES and traditional organic solvents. As carried out in the previous works, the water addition as an anti-solvent allowed a recovery yield of 73.6 wt.% of cynaropicrin. With both types of solvents, namely ILs and DES aqueous solutions, it is possible to increase the extraction yields of most studied biocompounds when compared to the yields obtained with volatile organic solvents and that the target compounds can be recovered by water addition, allowing the ILs and DES recycling.